The Presence of Women in the Dental Profession: A Global Survey - Guglielmo Campus; Anastasia Maclennan; Juliane von Hoyningen-Huene; Thomas Gerhard Wolf; Michele Aerden; Ihsane Benyahya; Jeannine Bonaventura; Eliane Lucia Koller Brolese; Jina Lee Linton; Ketevan Gogilashvili; Irene Marron-Tarrazi; Duygu Ilhan; et al. (Elsevier, 2024)
Objectives: The aim of this research was to acquire knowledge about the female dental workforce, identifying factors to pursue specialty training and career choices and working in dental institutions/associations. Methods: An original online questionnaire was developed, validated (n = 22), and sent to 189 member associations in 133 countries of the Women Dentists Worldwide section of the FDI World Dental Federation. Results: In all, 3232 female dentists from 81 countries participated. Results were divided into 5 geographic areas by continent. Difference in proportion amongst questionnaire items was evaluated with χ2 test or Fisher exact test. Ordinal multinomial linear regression analysis was performed to evaluate the association of questionnaire items with total work experience in dentistry (in years), motivation to study dentistry, type of specialisation, working hours per week, perception of female dentists about working hours, sex-based inequalities, job security after maternity leaves, as well as involvement in political organisations within their country of residence and their role in dental associations. A majority of participating female dentists are self-employed (57.7%), and 60.0% have 10 to 30 years of experience. The most popular form of practice is the single private practice (29.7%), followed by the group private practice (28.8%). Further, 44.8% work 31 to 40 h/wk, 29.1% part-time up to 30 h/wk, and 26.0% more than 40 h/wk. Conclusions: Women are still poorly represented in professional organisations, and few are officers in representative assemblies, members of the board, or president. Family life with children influences perceptions and has an impact on professional life, especially in academia and political/professional associations, so that taking on leadership positions poses additional challenges.